Leaves metabolomic profiling of Musa acuminata accessions using UPLC–QTOF–MS/MS and their antioxidant activity - Sonibare, M.A.; Ayoola, I.O.; Gueye, B.; Abberton, Michael T.; D'Souza, R.; Kuhnert, N. (Springer, 2018)
Musa acuminata (Musaceae) is a wild species native to South East Asia. In addition to its potential as a food crop, different non-food morphological parts of the plant have been investigated for various pharmacological activities, including anticholinesterase and antioxidant activity. This study aimed to characterize Musa leaf extracts based on their phenolic composition and their agro-morphological traits. A metabolomic approach was applied to discover biomarkers that can be used to separate eight accessions of the species originating from five different countries. Statistical analysis was employed for data analysis. The antioxidant activity and total phenolic content was measured by Ferric Reducing Antioxidant Power (FRAP) assay and Folin–Ciocalteu colorimetric method, respectively. Over 500 metabolites were observed. Thirty-one of them were important for defining variations among the accessions. The identities of some of these markers were confirmed based on their MS2 fragmentation. These include Quercetin O-rhamnoside-O hexoside (m/z 609), Kaempferol-3-O-rutinoside (m/z 593), Quercetin O hexoside (m/z 463), Hexadecanoic acid (m/z 255), Rhamnoside-O-rutinoside (m/z 623). Country of origin and methods of extraction did not play any significant role in the separation, although extraction of accessions by Soxhlet gave better yield (20.0–60.0%) than by sonication (18.4–23.0%). Accession TMp 24 from Nigeria gave the highest yield in both methods of extraction. The sonicated accession TMb 8 exhibited highest antioxidant activity having FRAP values of 49.14 mg GAE/g and 125.10 mg TROLOX/g. The next accession in FRAP activity was the sonicated leaf extract of TMb 116 with 31.69 mg GAE/g and 121.57 mg TROLOX/g. The PCA analysis allowed the separation of the accessions into two groups. The metabolomics approach was found to be informative as a screening tool of the Musa accessions. The extracts showed good antioxidant activity and can be a potential source of bioactive metabolites for industrial use.